The impact of contextual factors on entrepreneurial intention/ Raymond Bantin Clement - Clement, Raymond Bantin (2015)
Research in entrepreneurship field has magnetized the interest ofmany researchers as a tool of development for many countries. The study of the factors that leads people to become entrepreneurs has been a question ofmany researchers. This study explores the relationship between the contextual factors and entrepreneurial intention. As such, itfits squarely into the literature on the antecedents of entrepreneurship.. This study looks at the educational support, structural support, informal support, andformal support which are determinants of entrepreneurial intention. The data was gatheredfrom 250 undergraduate students at two of the university branch campuses in the Kota Samarahan, Sarawak.. Data collection was based on voluntary basis, informed consent, and anonymity. Regression analyses indicate that entrepreneurial intention is positively correlated with educational support and informal support. In thefinalsection, we discuss these results and discover afuture research agenda.